Culture potential and mechanism for forming a new progress ideal - Danilov, Alexander N. (Journal of the Belarusian State University. Sociology, 2020)
The article substantiates the theoretical foundations of the technology of forming a new progress ideal, reveals the role of culture and its potential in this process. The author justifies the existence and constant updating of the cultural code, its fundamental vital meanings and basic values, suggests the possibility of destructive changes when shifting the cultural status of basic values. The author considers of the article as the main conclusions, firstly, the mechanism of transition of society to a new state, where new types of sociality arise, fundamental life meanings and basic values are updated; secondly, the author shows that the formation of a new matrix of values and the renewal of life meanings is a condition for the transition to a new type of civilizational development, which is growing within modern society; thirdly, the revolution in the field of communication allows the transfer to the traditional cultural status of pseudocultural or extra-cultural values, thereby opening the way for the destruction of the foundations of culture.